KEGIATAN ANAK-ANAK DOWN SYNDROME SEKOLAH LUAR BIASA SINGARAJA DIMASA PANDEMI DALAM FOTOGRAFI DOKUMENTER - Mahendra, Kadek Yoga Riska; Saryana, I Made; Adityasmara, Farhan (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
Down syndrome is a genetic disorder that causes sufferers to have a low level of intelligence and experience a distinctive abnormality on the sufferer's face, the WHO data estimates that 3000 to 5000 babies are born with this condition each year, until now in Indonesia concern for children with Down syndrome is still relatively minimal, especially in Bali, due to lack of knowledge about children with special needs with Down syndrome, so many people still isolate children with Down syndrome. The purpose of the creator of using Down syndrome as an object of research is to change the stigma of people who consider Down syndrome to be small and to visualize